THE METROPOLITAN CONCEPT IN ERICH KASTNER'S BOOKS - Kirmizi, Bulent (Selcuk Univ, Fac Letters, 2016)
Metropolitan concept started to take part in literature quickly after the industrial revolution in 19. century in Europe. Metropolitan concept appears in people in two different ways. One of them is that, the big city is dirty, burdensome, fast, transformative and the other is that in a metropolitan city there are cinema, theater, shopping, social relationships and lots of other various opportunities. Metropolitan concept is proccessed majorly in 20. century novel and poetry. In German literature, Berlin Alexanderplatz (1929) of Alferd Dblin is shown as the most famous metropolitan novel. The conspicuous point here is that most of the literary works written about metropolitan after the First World War and before Second World War talk over Berlin as a metropolitan city. One of them is Eric Kastner's works which have been the subject of this study. Fabian, the most famous work of Kastner, also takes place in Berlin. Among his other works, the novel Emil and the poem Besuch vom Lande also take place in Berlin, too. 20th century literature takes its topic from metropolitan cities most of the time, because metropolitans leave profound impression on the person. The startup of migration from the village to the city with the industrial revolution and as a result of this, the increase of squatter settlement in the cities cause to the ghettoization. The struggle between social classes leads to the anxiety of getting to work on time and working harder. Besides, the longness of working hours, becoming distanced with the family members, the pursuit of happiness apart from family lead to alienation. All of these unfavorableness becomes a springe which the metropolitan cities prepare for the people who migrate from village to city.
Keywords: German literature; analysis of the novel; big city; New Objectivity